GOLD stage-specific phenotyping of emphysema and airway disease using quantitative computed tomography - Konietzke, Philip; Brunner, Christian; Konietzke, Marilisa; Wagner, Willi Linus; Weinheimer, Oliver; Heußel, Claus Peter; Herth, Felix J. F.; Trudzinski, Franziska; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver (Frontiers in Medicine, 2023)
Background: Abnormal lung function in chronic obstructive pulmonary disease (COPD) may be related to emphysema and airway obstruction. The relative contribution of these in dependence of GOLD-stage is mostly unknown. Methods: Non-contrast computed tomography (CT) of 522 patients with COPD at risk (former GOLD 0) and COPD stages GOLD 1-4 were evaluated using fully automated software for quantitative CT. Total lung volume (TLV), emphysema index (EI), mean lung density (MLD), and airway wall thickness (WT), total diameter (TD), lumen area (LA), and wall percentage (WP) were calculated for the entire lung, as well as for all lung lobes separately. Results from the 3rd-8th airway generation were aggregated (WT3-8, TD3-8, LA3-8, WP3-8). All subjects underwent full-body plethysmography (FEV1%pred). Results: EI was higher with increasing GOLD stages with 1.0±1.8% in GOLD 0, 4.5±1.8% in GOLD 1, 20.5±16% in GOLD 2, 33.27±13.3% in GOLD 3 and 41.4±10.0% in GOLD 4 subjects (p<0.001). WT3-8 showed no essential differences between GOLD 0 and GOLD 1, tented to be higher in GOLD 2 with 1.3±0.2mm, and was lower in GOLD 4 with 1.2±0.1mm (p=0.010 – p=0.974). In the upper lobes WP3-8 showed no significant differences between the GOLD stages (p=0.905 – p=0.948), while in the lower lobes the lowest WP3-8 was found in GOLD 0/1 with 49.9±6.5%, while higher values were detected in GOLD 2 with 52.0±6.3% and in GOLD 3/4 with 51.0±6.0% (p<0.05). In a multilinear regression analysis, the dependent variable FEV1%pred can be predicted by a combination of both the independent variables EI (p<0.001) and WP3-8 (p<0.001). Conclusion: QCT parameters showed a significant increase of emphysema from GOLD 0 - 4 COPD. Airway changes showed a different spatial pattern with higher values of relative wall thickness in the lower lobes until GOLD 2 and subsequent lower values in GOLD3/4, whereas there were no significant differences in the upper lobes. Both, EI and WP5-8 are independently correlated with lung function decline.